(3GdLQM hGdJYOjds - (3YHO GdQMef Hf eMeO CHj MGJe GHf EOQjS Hf GdefPQ GdJejej GdMfXdqj GdQGRqj, CHh eMeO,J (B327 (3g` s
(3ChdgG (B:s
(3ef YHO Gddg Hf gGfF GdCROi s
(3BNQgG (B:s
(3Edi YeQh Hf SYjO ehdi Kbja s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B324 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B170s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B106 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs